Risk analysis of corroded oil and gas pipeline using bayesian network approach - Nadhirah Aqilah, Azizuddin; Nurul Sa'aadah, Sulaiman (2021)
The pipeline failure due to corrosion is the most significant factor in oil and gas pipeline failure which causing massive property loss and damage to the environment, resulting in liquid leakage and gas release. The main objective is to conduct risk assessment of corroded oil and gas pipeline using Bayesian network approach in order to solve the corrosion problem form the root causes.